Psychoeducation with problem-solving (PEPS) therapy for adults with personality disorder: a pragmatic randomised controlled trial to determine the clinical effectiveness and cost-effectiveness of a manualised intervention to improve social functioning - McMurran, Mary; Crawford, Mike J.; Reilly, Joe; Delport, Juan; McCrone, Paul; Whitham, Diane; Tan, Wei; Duggan, Conor; Montgomery, Alan A.; Williams, Hywel C.; Adams, Clive E.; Jin, Huajie; et al. (NIHR Health Technology Assessment Programme, 2016)
Main outcome measures: The primary outcome was measured by the Social Functioning Questionnaire (SFQ). Secondary outcomes were service use (general practitioner records), mood (measured via the Hospital Anxiety and Depression Scale) and client-specified three main problems rated by severity. We studied the mechanism of change using the Social Problem-Solving Inventory. Costs were identified using the Client Service Receipt Inventory and quality of life was identified by the European Quality of Life-5 Dimensions questionnaire. Research assistants blinded to treatment allocation collected follow-up information. Results: There were 739 people referred for the trial and 444 were eligible. More adverse events in the PEPS arm led to a halt to recruitment after 306 people were randomised (90% of planned sample size); 154 participants received PEPS and 152 received usual treatment. The mean age was 38 years and 67% were women. Follow-up at 72 weeks after randomisation was completed for 62% of participants in the usual-treatment arm and 73% in the PEPS arm. Intention-to-treat analyses compared individuals as randomised, regardless of treatment received or availability of 72-week follow-up SFQ data. Median attendance at psychoeducation sessions was approximately 90% and for problem-solving sessions was approximately 50%. PEPS therapy plus usual treatment was no more effective than usual treatment alone for the primary outcome [adjusted difference in means for SFQ –0.73 points, 95% confidence interval (CI) –1.83 to 0.38 points; p = 0.19], any of the secondary outcomes or social problem-solving. Over the follow-up, PEPS costs were, on average, £182 less than for usual treatment. It also resulted in 0.0148 more quality-adjusted life-years. Neither difference was statistically significant. At the National Institute for Health and Care Excellence thresholds, the intervention had a 64% likelihood of being the more cost-effective option. More adverse events, mainly incidents of self-harm, occurred in the PEPS arm, but the difference was not significant (adjusted incidence rate ratio 1.24, 95% CI 0.93 to 1.64). Limitations: There was possible bias in adverse event recording because of dependence on self-disclosure or reporting by the clinical team. Non-completion of problem-solving sessions and non-standardisation of usual treatment were limitations. Conclusions: We found no evidence to support the use of PEPS therapy alongside standard care for improving social functioning of adults with personality disorder living in the community. Future work: We aim to investigate adverse events by accessing centrally held NHS data on deaths and hospitalisation for all PEPS trial participants.